Desempenho de lima ácida Tahiti sobre diferentes porta-enxertos - Bettini, Bruna Aparecida (2019)
The Tahiti acid lime, popularly known in Brazil as Tahiti acid lime, is one of the most produced fruits in the state of São Paulo, with the northwest region as the main producer pole. However, there are many losses due to the large number of diseases and pests. To reduce these losses, the genetic variability of rootstocks in the market is of extreme importance. The objective of this work was to evaluate the performance of the Tahiti acid lime in different rootstocks. The experiment was conducted at the Paulista Agency of Technology of Agribusiness, located in the municipality of Pindorama, São Paulo, Brazil, in March 2013, with spacing of 7.0 m x 4.0 m, in a randomized block with three replicates and one plant per plot. The vegetative development, plant phenology and production, physicochemical characteristics of fruits, post-harvest fruit durability, canopy/rootstock compatibility, drought tolerance, detection of Candidatus Liberibacter asiaticus (CLas), causal agent of Huanglongbing (HLB), were evaluated in a Tahiti acid lime (IAC-5), grafted on thirteen citrandarins, hybrids of Sunki mandarin x Poncirus trifoliate (H), Rangpur lime Citrus limonia (L.) Osbeck (RL), Poncirus trifoliata Flying Dragon (FD) and Sunki mandarin (SM). The rootstocks H14, H47, H135, H152, FD and SM induced the smallest size in plants of Tahiti acid lime, while the rootstocks H5, H10, H42, H70, H73, H121, H145, H150, H173 and RL a larger size. Consequently, the ones that induced smaller size to Tahiti acid lime scion were the most susceptible to the water deficit. The rootstocks H10 and H121 provided higher productivity of Tahiti acid lime fruit, being similar to the RL, but when we consider the adjusted spacing, besides these mentioned rootstocks, the rootstocks H70, H73, H150, H5, H152 and H42showed also good productivity. For the phenology, rootstocks induced fruits precociously and belatedly. In the physico-chemical evaluation, there was only statistical difference for the total soluble solids and ratio, where rootstocks H14, FD and SM were the ones that provided higher total soluble solids content to Tahiti acidic fruit and H173 the highest value of ratio. For post-harvest durability the Tahiti acid lime fruits grafted on the rootstock H10 obtained good characteristics and could be stored up to 47 days without loss of quality. The Tahiti acid lime was compatible with all rootstock studied and citrandarin 14 was the only one that showed late onset of HLB symptoms in Tahiti acid lime plants grafted on it. Therefore, citrandarins may be considered as new alternative rootstocks for the Tahiti acid lime.